2021
DOI: 10.18844/cjes.v11i4.347
|View full text |Cite
|
Sign up to set email alerts
|

Do years of teaching experience make a difference for teachers working in Abu Dhabi government schools?

Abstract: In Abu Dhabi, the capital of the United Arab Emirates, subject teachers of English medium in government schools are recruited from overseas and have a wide range of years of teaching experience. Research is divided into whether or not years of experience necessarily translates into a positive correlation with student-centred classroom practice such as the use of hands-on learning and inquiry-based approaches to learning in science. Abu Dhabi is in the process of dramatically overturning its education system, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…It seems that length of working experience and higher educational qualification gave benefit to their competence. This finding cohered with previous research reporting that length of working experience gave teachers more experience and made them confidence in their own abilities (Dickson, McMinn, & Kadbey, 2019); short experience of novice teacher in teaching affect their efficacy in performing expected task where guidance was still needed (Faez & Valeo, 2012). However, other studies informed that self-efficacy of teachers contribute more on students' achievement rather than teachers' length of teaching experience and qualification (Guo, Connor & Morrison, 2012) and teachers' advanced degrees did not necessarily affect students' achievement although teachers teaching experience may influence students achievement (Buddin & Zamarro, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…It seems that length of working experience and higher educational qualification gave benefit to their competence. This finding cohered with previous research reporting that length of working experience gave teachers more experience and made them confidence in their own abilities (Dickson, McMinn, & Kadbey, 2019); short experience of novice teacher in teaching affect their efficacy in performing expected task where guidance was still needed (Faez & Valeo, 2012). However, other studies informed that self-efficacy of teachers contribute more on students' achievement rather than teachers' length of teaching experience and qualification (Guo, Connor & Morrison, 2012) and teachers' advanced degrees did not necessarily affect students' achievement although teachers teaching experience may influence students achievement (Buddin & Zamarro, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Hence, Hypothesis 2: There is no relationship between teacher written feedback self-efficacy and teaching experience was accepted. Similarly, findings showed that teachers' teaching experience negatively influenced teachers' self-efficacy in teaching practices Dickson, M., McMinn, M. & Kadbey, H., 2019). However, the findings from the previous study conducted by Lumpe, Czerniack, Haney & Beltyukova (1999) shows that the number of years of teaching was significantly affected context selfefficacy beliefs.…”
Section: Self-efficacy and Teaching Experiencementioning
confidence: 83%
“…According to Huberman (1989), the teachers sometimes begin to reach out for help after the first or two years of teaching. They can take stock of their teaching a little at this stage, past the frenzy and challenges of the novice years (Dickson, M., McMinn, M. & Kadbey, H., 2019). However, more experienced teachers may have a desire to update their skills because the skills they acquired during teacher training begin to fade (Badlishah & Majid, 2016;Greenwood, 2003).…”
Section: Teachers' Demographic Factors and Self-efficacymentioning
confidence: 99%
“…The number of courses will affect teachers' evaluation and satisfaction with teaching, in which too many courses will consume too much energy of teachers and cause them to feel burnout (Ismayilova and Klassen, 2019). The years of teaching also affects teacher's teaching practice and teaching efficacy and then affects their teaching evaluation (Dickson et al , 2019). It has been found that self-assessments involving a wide range of personality traits and specific core traits are significantly associated with job satisfaction, job performance and life satisfaction (Judge et al , 2003).…”
Section: Literature Reviewmentioning
confidence: 99%